Is intimate partner violence vertically transmitted among women in sub-Saharan Africa? Evidence from demographic health surveys between 2010 and 2019 - Oluwatobi Abel Alawode; Obasanjo Afolabi Bolarinwa; Julia Marie Hajjar; Stephen Okechukwu Chukwudeh; Sanni Yaya (BMC, 2023)
Abstract Background Violence against women is a major human rights violation, and the continuous occurrence of this can have many implications for women's social and health outcomes. The experience of violence from an intimate partner could be more intriguing, especially if such women experienced their mother's intimate partner violence (IPV) issues. Thus, this study examined the vertical transmission of IPV among women in sub-Saharan Africa (SSA). Methods A total of 97,542 eligible women were drawn from 27 countries in SSA using a retrospective secondary dataset from Demographic Health Surveys conducted between 2010 and 2019. Multivariable analysis was employed to determine the association between the vertical transmission of IPV from mother to daughter and the covariates associated with IPV in SSA at p < 0.05. Results The results showed that 40% of the respondents had experienced lifetime IPV, whilst 25% of those women reported that their mothers experienced it in childhood in SSA. Country-specific variations showed the highest prevalence of IPV experienced in Sierra Leone (60%) and the lowest in Comoros (9%). Results from model 1 showed that women who reported that their mothers experienced IPV were found to be significantly more than two times more likely to have experienced any form of IPV compared to those whose mothers did not (aOR = 2.66; 95% CI: 2.59-2.74), after adjusting for cofounders in Model 2, the result still showed that women who reported that their mothers experienced IPV were found to be significantly more than two times more likely to have experienced any form of IPV compared to those whose mothers did not (aOR = 2.56; 95% CI: 2.48-2.63). On the other hand, women with higher-educated partners, women in rural areas, and those from female-headed households were less likely to experience IPV. Conclusion This study concluded that women whose mothers experienced IPV were more likely to have experienced IPV. Our study also identified that education, rural areas, and female-headed households were protective factors against experiencing IPV. To address the groups of women at higher risk for experiencing IPV, we recommend ensuring that girls complete their education to promote greater wealth and resources.